The Acceptance Model of Mobile Shopping Apps in China - Xiaojian Lin; Yingming Qiu; Singha Chaveesuk; Wornchanok Chaiyasoonthorn (My University, 2021)
With the higher users’ rate of mobile internet technology, more and more Chinese people start to use smartphones. E-commerce is gradually changing to mobile commerce in China. As a new shopping tool, mobile shopping Apps are more and more popular in China. The challenges of promoting mobile shopping Apps have brought challenges to the company promoting it. In this study, we propose a conceptual framework of the adoption model of mobile shopping (M-shopping) Apps based on UTAUT2 integrated with factor Corporate Reputation and factor Personal Innovativeness in IT to examine the correlative factors influencing users' willingness to use the mobile shopping applications before quantitative analysis, providing some suggestions on how to improve M-shopping Apps for the retailers and Apps developers.
Keywords: Digital Marketing and Social Media; Technology Adoption and User Behaviour; Customer Service Quality and Loyalty